Prevalence of Diseases and Pattern of Medicine Used by Retired Armed Forces Personnel Attending at a Military Hospital (Journal of Armed Forces Medical College, Bangladesh, 2022)
Introduction: Retired armed forces personnel constitute a large group of population whose treatment is ensured by the armed forces. Their disease prevalence and medicine use pattern will help the authority to take more effective decision for managing their ailments.Objectives: To observe the medicine use patterns and disease prevalence among retired armed forces personnel.Materials and Methods: This cross-sectional prescription evaluation was carried out on 546 prescriptions obtained from Others Rank (ORs) Pharmacy of Combined Military Hospital (CMH), Dhaka from mid June to mid July, 2020. According to World Health Organization’s (WHO) core prescribing indicators analysis, number of drugs/prescription, percentage of drug written in generic name, percentage of prescription with an injection, percentage of prescription with antimicrobials and percentage of prescription containing local purchase drugs were calculated.Results: All the patients were male and their age ranges from 38 to 84 years with mean age of 58.6 years. Half of the patients were in 55 to 64 years age groups. About 43% patients had two chronic diseases. The average number of drugs per prescription was 5.3 drugs. Patients with single disease required less number of drugs/prescription (3.7) compared to patients having two (5.6) and multiple diseases (8.2). Hypertension was the most frequent diagnosis (n=330) and diabetes was the 2nd frequent diseases (n=307).Conclusion: The average number of drug per prescription corresponds to the number of diseases. The retired armed forces personnel with active adult life (55-64 years) suffer more than the elderly (more than 65). Hypertension and diabetes mellitus are the most prevalent diseases.JAFMC Bangladesh. Vol 18, No 1 (June) 2022: 12-15